Empty Categories in the Hindi-Urdu binaa Participle Clause - Davison, Alice (Lingua Posnaniensis, 2013)
Hindi-Urdu has an oblique participle construction meaning ‘without’, which resembles a parasitic gap construction in other languages. These other languages, like English, have obligatory movement to the left which is a condition on a parasitic gap, as in wh- question sentences. But in Hindi-Urdu, questions do not require leftward movement, allowing the question word to stay in situ. In addition, this participle is possible with statements as well, suggesting that Hindi-Urdu does not have parasitic gaps or obligatory A ’ movement. T his paper explores the actual nature of this participle, concluding that it has a PRO subject and null pronoun object.